2010
DOI: 10.3390/molecules15129391
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Essential Oil of Carum Carvi Fruits from China and Its Main Components against Two Grain Storage Insects

Abstract: During our screening program for agrochemicals from Chinese medicinal herbs and wild plants, the essential oil of Carum carvi fruits was found to possess strong contact toxicity against Sitophilus zeamais and Tribolium castaneum adults, with LD50 values of 3.07 and 3.29 μg/adult, respectively, and also showed strong fumigant toxicity against the two grain storage insects with LC50 values of 3.37 and 2.53 mg/L, respectively. The essential oil obtained by hydrodistillation was investigated by GC and GC-MS. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 42 publications
3
49
0
5
Order By: Relevance
“…The application of carvone or limonene causes an increase in activity of the detoxifying enzyme GST in the liver of mice (Zheng et al 1992). Insecticidal activity of caraway essential oil, carvone, and limonene against sitophilus oryzae, s. zeamais, and tribolium castaneum has also been reported (Abdelgaleil et al 2009;Fang et al 2010). Carvone is also an effective repellent to t. castaneum (Caballero-Gallardo et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The application of carvone or limonene causes an increase in activity of the detoxifying enzyme GST in the liver of mice (Zheng et al 1992). Insecticidal activity of caraway essential oil, carvone, and limonene against sitophilus oryzae, s. zeamais, and tribolium castaneum has also been reported (Abdelgaleil et al 2009;Fang et al 2010). Carvone is also an effective repellent to t. castaneum (Caballero-Gallardo et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The presence of a signal at δ 5.81 ppm (1H, m, H-2) indicates the presence of a double bond, which is most probably at C-1, that was confirmed from the downfield shift of Me-7 (δ 2.02 ppm). The 13 C-NMR spectrum of the compound confirmed the presence of a double bond by the two olefinic carbons at δ 114.0 and 139.2 ppm assigned to C-2 and C-1, respectively (Fang et al, 2010). From the aforementioned data, compound 5 was identified as dihydrolimonene.…”
Section: Resultsmentioning
confidence: 65%
“…Moreover, the peak at m/z 67 (loss of proton from fragment at m/z 68) and the peak at m/z 95 represents the loss of isopropyl group (M-43) + . The characteristic peaks at m/z 80 represents (95-CH 3 ) + , the peak at m/z 55 represents a retro-Diels-Alder fragmentation of fragment at m/z 80 and the peak at m/z 54 represents the loss of proton from fragment at m/z 55 (Crews et al, 1998;Fang et al, 2010;Silverstein and Webster, 1996). 13 C-NMR spectrum of compound 5 showed 10 carbons indicating that it is a monoterpene.…”
Section: Resultsmentioning
confidence: 99%
“…A. polystachya showed the highest toxicity (Table 5). Carvone, the main compound of A. polystachya, has been found to be toxic against diverse insects, for example, Fang et al [25] found strong contact toxicity of carvone and limonene, against Sitophilus zeamais and T. castaneum. Moreover, carvone caused the highest mortality against larvae of T. castaneum among the several monoterpenes evaluated (LC 50 = 19.8 g/cm 2 ) [26].…”
Section: Resultsmentioning
confidence: 99%